Development & exploitation of gene tools for metabolic engineering in saccharolytic Clostridia - Ehsaan, Muhammad (2013)
C. acetobutylicum A TCC 824 is a well characterized microorganism known for its ability to produce solvents using the Acetone-Butanol-Ethanol (AB E) fermentation process. It can utilize a variety of Cs and C6 sugars, but cannot directly access the complex lignocellulose plant cell wall material which is the most abundant source of carbon in nature. Sophisticated genetic tools are required to enhance the substrate utilisation ability of the organism by incorporating synthetic operons using a synthetic biology approach. Efficient tools were developed for making precise alterations to the C. acetobutylicum genome using either heterologous pyrE or codA genes as counterselection markers. In the case of the former, the utility of the method was also demonstrated in Clostridium difficile. The robustness and reliability of the methods were demonstrated through the creation of in-frame deletions in two genes (spoOA, amylase) using pyrE and also two genes (Cac1502 and Cac2071 (spoOA) using codA. The pyrE system is reliant on the initial creation of a pyre deletion mutant using Allele Coupled Exchange (ACE), that is auxotrophic for uracil and resistant to fluoroorotic acid (FOA). This enables the subsequent modification of target genes by allelic exchange using a heterologous pyre allele from C. sporogenes as a counter-/negative-selection marker in the presence of FOA. Following modification of the target gene, the strain created is rapidly returned to uracil prototrophy using ACE, allowing mutant phenotypes to be characterised in a pyrE proficient background. Crucially, wild-type copies of the inactivated gene may be introduced into the genome using ACE concomitant with correction of the pyrE allele. This allows complementation studies to be undertaken at an appropriate gene dosage, as opposed to the use of multicopy autonomous plasmids. The rapidity of the 'correction' method (5-7 days) makes pyrE strains attractive hosts for mutagenesis studies.